Attenuation of strong earthquake ground motion – I: Dependence on geology along the wave path from the Hindu Kush subduction to Western Himalaya. Issue 114 (November 2018) - Gupta, I.D.; Trifunac, M.D.
Abstract: The common approach to describing the attenuation of strong earthquake ground motion has been in terms of a variable that measures the length of the wave path between the earthquake source and the recording site. Although in some published empirical scaling equations, soil and geological conditions at the recording site also have been included via simple site-specific parameters, however, with few exceptions, the geology along the wave propagation path has been generally ignored. This has resulted in excessive residuals of predicted amplitudes and increases the uncertainty in the end results—namely, prediction of design amplitudes for earthquake-resistant structure design. In this paper, we describe one example in which the dependence of attenuation equations on the geology can be demonstrated due to a clear separation in the location of contributing earthquake sources and the associated differences in the geological environment along the wave paths. Our example shows the advantages of including a geologic description along the path of seismic waves and thus design amplitude predictions can be developed more realistically and with certainty for a given region. Highlights: Frequency dependent attenuation of strong motion from Hindu Kush earthquakes. Scaling equations for Fourier and PSV Spectra from Hindu Kush earthquakes. Scaling strong motion amplitudes in northwest India up to distances of 900 km. Tests of empirical Fourier and PSV spectra at long periods in terms of seismic moment.